Exigência de energia metabolizável, lisina e metionina+cistina digestíveis para codornas de corte em fase de crescimento - Scherer, Carina (2009)
Six experiments were carried out to determine the metabolizable energy (ME), digestible lysine (DL) and digestible methionine+cystine (M+C) requirements for growing meat quail. In the first experiment, the objective was to determine the ME requirements from 1 to 14 days of age, using 1,140 meat quail distributed in a completely randomized design, with five treatments (2,750; 2,850; 2,950; 3,050 and 3,150 kcal of ME/kg of diet), six replications and 38 poultries per experimental unit. There was a decrease (P<0.05) on body weight (BW), feed intake (FI), weight gain (WG) and cuts water content, with the ME levels increase. The feed: gain ratio (F:G), daily protein accretion (DPA), protein accretion efficiency (PAE) and cuts energy retained (CER) showed a quadratic effect (P<0.05) with estimative of 2,997 kcal of ME/kg for the best F:G ratio. In the second experiment, the objective was to determine de ME requirements from 15 to 35 days of age, using 600 meat quail, distributed in a completely randomized design, with six treatments (2,800; 2,900; 3,000; 3,100; 3,200 and 3,300 kcal of ME/kg of diet), five replications and 20 poultries per experimental unit. There was a decrease (P<0.05) on FI, F:G ratio and cuts water and CP contents with diets ME levels increase. The BW, WG and daily fat accretion (DFA) showed a quadratic effect (P<0.05), with estimative of 3,036 kcal of ME/kg for maximum WG. In the third experiment, the objective was determine de DL requirements, from 1 to 14 days of age, using 1,785 meat quail, distributed in a completely randomized design, with seven treatments (1.16; 1.31; 1.46; 1.61; 1.76; 1.91 and 2.06% of DL), five replications and 51 poultries per experimental unit. There was an increase (P<0.05) on BW, WG, DPA and CER with diets DL levels increase. The FI intake and F:G ratio showed a quadratic effect (P<0.05), with estimative of 1.88% of DL requirement for the best F:G ratio. In the fourth experiment, the objective was to determine the DL requirement, from 15 to 35 days of age, using 875 meat quail, distributed in a completely randomized design, with seven treatments (1.00; 1.16; 1.32; 1.48; 1.64; 1.80 and 1.96% of DL), five replications, with 25 poultries each one. There was an increase (P<0.05) on BW, WG, FI and DPA with diets DL levels increase. The F:G ratio improved (P<0.05) with the DL levels increase, whose data were adjusted with LRP model, estimating the level of 1.73% of DL. In the fifth experiment, the objective was to determine the digestible M+C requirement, from 1 to 14 days of age, using 1,250 meat quail, distributed in a completely randomized design, with five treatments (1.33; 1.45; 1.56; 1.67; 1.79% of digestible M+C), five replications and fifth poultries per experimental unit. There were a quadratic effect (P<0.05) on BW, WG and F:G ratio, estimating the levels of 1.47, 1.47 and 1.57%, for highest BW, WG and best F:G ratio, respectively. The estimated level of digestible M+C requirement for meat quail, from 1 to 14 days of age, was 1.57%. In the sixth experiment, the objective was to determine de digestible M+C requirement, from 15 to 35 days of age, using 825 quails meat, distributed in a completely randomized design, with five treatments (1.24; 1.35; 1.45; 1.56 and 1.66% of digestible M+C) and five replications, with 33 poultries each one. There was a quadratic effect (P<0.05) on BW, WG, F:G ratio, MC and NB, estimating the levels of 1.51, 1.51, 1.52, 1.50 and 1.50%, respectively. The estimated level of digestible M+C requirement for meat quail, from 15 to 35 days of age, is 1.52%.